From damsel to man in distress: traditional Gothic in the novel L'incanto del pesce luna - Dinić, Miona (Romanica Olomucensia, 2024)
Ade Zeno's novel L'incanto del pesce luna (The Enchantment of the Sunfish) reinvents the characteristics of traditional Gothic fiction within a contemporary context. Zeno adopts the well-known literary trope of a damsel in distress and reworks it by introducing the figure of the (female) vampire as a menacing element. Thus, he creates a narrative that blends supernatural elements with a disquieting yet recognisable reality. This article will analyse how Ade Zeno employs certain traditional Gothic elements within a contemporary setting while simultaneously exploring the concept of the monstrous. A general introduction to Gothic literature is provided, followed by a summary of the novel, and then a comparison of the Gothic elements with their traditional origins is conducted. Zeno's work offers a profound reflection on the delicate boundary between humanity and monstrosity, challenging conventional concepts of morality and identity. In addition to the Gothic elements, the narrative exposes the hypocrisy and immorality of human beings, suggesting that the distinction between humanity and monstrosity is not as clear-cut as commonly believed. Through a skilful manipulation of Gothic elements, Ade Zeno prompts critical reflection on the complex nature of humanity and the ambiguous moral dimensions that characterise its existence. L'incanto del pesce luna emerges not only as a contemporary Gothic novel but also as a challenge to the conventional perception of what constitutes true monstrosity, delving into the depths of the human psyche.
Keywords: gothic; Ade Zeno; monstrous; fantasy; novel